POSTOPERATIVE COMPLICATION AMONG PATIENTS WHO UNDERWENT DECOMPRESSIVE CRANIECTOMY FOR TRAUMATIC BRAIN INJURY - JAMALI , MS; KORAI , PJ; HUSSAIN , S; JAMALI , MA; JAWAID , I; SHAUKAT , S (Biological and Clinical Sciences Research Journal, 2024)
Decompressive craniectomy is a life-saving procedure used to manage severe traumatic brain injury (TBI). While it effectively reduces mortality, the procedure is associated with multiple postoperative complications, which may impact patient recovery and outcomes. Understanding the frequency and nature of these complications is critical for improving patient care. Objective: The objective of this study was to determine the frequency of postoperative complications in patients who underwent decompressive craniectomy for traumatic brain injury at a tertiary care hospital in Karachi. Methods: This descriptive cross-sectional study was conducted at SMBB Trauma Centre, Civil Hospital Karachi, from February 20, 2020, to August 20, 2020. A total of 98 patients who underwent decompressive craniectomy for TBI were included. Data were collected on demographic variables, clinical parameters, and postoperative complications. The mean age, length of hospital stay, duration of injury, and surgery duration were analyzed. Statistical analysis was performed using descriptive statistics. Results: The mean age of the patients was 45.14 ± 9.49 years, with a mean hospital stay of 10.72 ± 6.24 days, mean duration of injury of 8.41 ± 4.69 hours, and mean surgery duration of 4.87 ± 2.14 hours. Of the 98 patients, 60 (61.2%) were male and 38 (38.8%) were female. The most common postoperative complication was subdural effusion, affecting 37 patients (37.76%), followed by contusion expansion in 19 patients (19.39%), external cerebral herniation in 16 patients (16.33%), syndrome of the trephined in 12 patients (12.24%), epilepsy in 7 patients (7.14%), and cerebrospinal fluid (CSF) leakage in 4 patients (4.08%). Conclusion: Decompressive craniectomy is an established treatment for reducing mortality in patients with traumatic brain injury. However, the procedure is associated with significant postoperative complications, such as subdural effusion and contusion expansion, which require timely identification and management. Despite its benefits, the risks associated with decompressive craniectomy necessitate careful postoperative monitoring to improve patient outcomes.